Evaluation of Membrane Gas Absorption Performance by Using Various of Liquid Absorbents - Sunarti, Abd Rahman; Ahmad, A. L. (IJEIT, 2015)
Membrane gas absorption (MGA) can overcome the major drawbacks of the processes have been used commercially for the removal of CO2. However, there are still many challengesin the operation of MGA in order to develop hydrophobic membrane and choose the best liquid absorbent to suit a whole range of promising MGA application, which is the main focus of this research. Performance in batch of MGA was carried out using deionized water, AMP and DEA as liquid absorbent. It was observed that the mass transfer rate of CO2 increases with the liquid absorbent flow rate, gas feed flow rate, liquid absorbent concentration and CO2 concentration at inlet gas. When the CO2 concentration increases from 20 vol. % to 100 vol. %, CO2 absorption using DEA was superior to AMP and deionized water.